2007
DOI: 10.4102/curationis.v30i4.1115
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of breast self-examination in women in Sierra Leone

Abstract: Curationis 30(4): 38-44This research is a follow up of a Breast Week which was organized in Freetown, Sierra Leone. The specific objective o f this study was to assess the effectiveness of the knowledge and teachings given to the women who participated in this project. A quantitative approach with an exploratory descriptive design was adopted and an observational checklist guided the data collection process. A sample size o f 120 women (10%) who participated in the Breast Week was obtained through systematic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…Level of awareness regarding how to perform simple life-saving diagnostic breast checks such as BSE further compounds the problem of late detection. Empowerment of women with information on BSE is of paramount importance, especially in countries without modern technologies for breast cancer screening (Shepherd & McInerney 2007 :38). South African rural communities have limited technological resources, but BSE can contribute greatly if women are informed about this technique and regular practice would reduce late presentation.…”
Section: Introductionmentioning
confidence: 99%
“…Level of awareness regarding how to perform simple life-saving diagnostic breast checks such as BSE further compounds the problem of late detection. Empowerment of women with information on BSE is of paramount importance, especially in countries without modern technologies for breast cancer screening (Shepherd & McInerney 2007 :38). South African rural communities have limited technological resources, but BSE can contribute greatly if women are informed about this technique and regular practice would reduce late presentation.…”
Section: Introductionmentioning
confidence: 99%
“…Of these 29 studies, 13 were categorised as having low risk of bias,36–48 10 were categorised as having moderate risk of bias,49–58 and 6 were unable to be assessed due to a lack of detailed evaluation of the developed approaches 59–64. The raw scores of these studies were shown in online supplemental file 3.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 29 studies included in the synthesis, 16 focused on cancer,36–42 49–54 59–61 5 on respiratory diseases,43 44 55 62 63 3 on cardiovascular diseases45 46 64 and 1 each on other health conditions including concussion,56 labour,57 malaria,47 neonatal illness48 and RA 58. Six were community-based studies engaging various parties (eg, educators and women leaders) in the communities and employing different outreach efforts (eg, flyers and radio advertisements),37 39 47 52 61 64 among which two involved training of both laypersons and health providers 47 64. Five studies reported only the development of approaches,59 60 62–64 while the remaining 24 reported both the development and evaluation of approaches using quantitative and/or qualitative measures (online supplemental file 4).…”
Section: Resultsmentioning
confidence: 99%
“…Level of awareness regarding how to perform simple life-saving diagnostic breast checks such as breast self-examination (BSE) further compounds the problem of late detection. Empowerment of women with information on BSE is of paramount importance, especially in countries without modern technologies for breast cancer screening [17]. Most of the Nigerian rural communities lacked the required technological resources [18], but BSE can contribute greatly if women are informed about this technique, and regular practice would reduce late presentation [14].…”
Section: Introductionmentioning
confidence: 99%